Perancangan Baru Gowork Coworking Space Di Bandung Dengan Pendekatan Uses And Activities - Ajeng Alfira, Aisya; Nur Hadiansyah, Mahendra; Salayanti, Santi (Telkom University, 2024)
Coworking spaces have become an important phenomenon in the modern world of work, as they provide a space where individuals and teams can work collaboratively and independently. This research presents a new coworking space design in Bandung by adopting a place and activity use approach. This approach aims to create spaces that are not only functional, but also inspire and support creativity and productivity. Through environmental analysis research and potential user needs, and design spaces that can accommodate various types of activities and functions. This coworking space aims to become a dynamic center of activity with various zones, from open work areas to creative corners and meeting rooms designed to foster collaboration. 'Placemaking' describes the role of space as a place that can create unique experiences and enhance the well-being of its occupants. With this approach, hope that this coworking space will not only meet the functional needs of its users, but also become a central place for social interaction and innovation. By integrating uses and activities into spatial design, this project aims to respond to the dynamics of modern work development and support the growth of the professional community in Bandung. Keywords: coworking space, collaboration, productivity, activity and function